Resource allocation to growth or luxury consumption drives mycorrhizal responses. (1st August 2019) - Riley, Rohan C.; Cavagnaro, Timothy R.; Brien, Chris; Smith, F. Andrew; Smith, Sally E.; Berger, Bettina; Garnett, Trevor; Stonor, Rebecca; Schilling, Rhiannon K.; Chen, Zhong‐Hua; Powell, Jeff R.
Abstract: Highly variable phenotypic responses in mycorrhizal plants challenge our functional understanding of plant‐fungal mutualisms. Using non‐invasive high‐throughput phenotyping, we observed that arbuscular mycorrhizal (AM) fungi relieved phosphorus (P) limitation and enhanced growth of Brachypodium distachyon under P‐limited conditions, while photosynthetic limitation under low nitrogen (N) was exacerbated by the fungus. However, these responses were strongly dependent on host genotype: only the faster growing genotype (Bd3‐1) utilised P transferred from the fungus to achieve improved growth under P‐limited conditions. Under low N, the slower growing genotype (Bd21) had a carbon and N surplus that was linked to a less negative growth response compared with the faster growing genotype. These responses were linked to the regulation of N : P stoichiometry, couples resource allocation to growth or luxury consumption in diverse plant lineages. Our results attest strongly to a mechanism in plants by which plant genotype‐specific resource economics drive phenotypic outcomes during AM symbioses.